2006
DOI: 10.1002/ijc.22417
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequality and short‐term outcome in Hodgkin's lymphoma

Abstract: Socioeconomic status (SES) is a determinant of outcome in various types of cancer. The aim of this study is to analyze the impact of the SES in Hodgkin's lymphoma (HL). From 2001From to 2005 consecutive patients were prospectively followed in 5 institutions. Patients answered a questionnaire with a set of items used to determine the SES, and were then divided in 2 groups according to their SES score. There were 151 patients (78%) with a higher SES and 43 patients (22%) with a lower SES. The complete remissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 12 publications
1
23
0
1
Order By: Relevance
“…Controversies exist regarding the value of CT scans [9,10] and PET scans [11] in the follow-up of Hodgkin patients. Until such time that their value is clearly established, they should be used judiciously, on the basis of an initial clinical evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Controversies exist regarding the value of CT scans [9,10] and PET scans [11] in the follow-up of Hodgkin patients. Until such time that their value is clearly established, they should be used judiciously, on the basis of an initial clinical evaluation.…”
Section: Discussionmentioning
confidence: 98%
“…Although we did not have health insurance information for AYAs throughout our study period, it is likely that factors beyond health insurance are influencing these race/ethnicity and neighborhood SES associations. Inadequate long-term follow-up in patients could result in a delay in diagnosing and treating complications (27), particularly for AYAs, who tend to lack knowledge about their higher risk for developing complications (2830). Financial concerns, including lost wages, copayments, high deductibles, childcare and transportation costs (24, 31–33) can be burdensome and influence follow-up care, particularly for AYAs with financial limitations (e.g., debt from college or starting a career).…”
Section: Discussionmentioning
confidence: 99%
“…Results show that health-related QoL is affected by chronic medical morbidity in elderly patients and the level of education has weak but unique contributions to physical functioning, health perception and mental health [31]. A study on patients affected by Hodgkin's lymphoma demonstrated that low SES leads to a trend towards a lower complete remission to the disease when compared with high SES [32]. These findings support the view that cancer patients with low SES are more likely to report bad health outcomes than patients with high SES.…”
Section: Introductionmentioning
confidence: 99%